2017
DOI: 10.1590/0104-6632.20170342s20150613
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of solid-state fermentation for bioherbicide production by Phoma sp .

Abstract: -In this work the bioherbicide production from Phoma sp. by solid-state fermentation was optimized. Agroindustrial residues such as bagasse, soybean bran and corn steep liquor were used as substrate. The bioherbicide was extracted from the fermented solid and the supernatant was applied for the control of the target plant. The evaluated responses in the bioassay were plant height, root length, fresh and dry weight, number of flowers and phytotoxicity. The results in the bioassays demonstrated that the bioherbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…A significant difference (p < 0.05) was observed for plant height with the application of the P. dimorpha fermented broth on S. obtusifolia plants, resulting in a lower height (Table 4). Similar results were observed by Klaic et al (2017), who found a reduction of 30 % in the plant height of the bioindicator C. sativus, when submitted to the same fermented broth.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…A significant difference (p < 0.05) was observed for plant height with the application of the P. dimorpha fermented broth on S. obtusifolia plants, resulting in a lower height (Table 4). Similar results were observed by Klaic et al (2017), who found a reduction of 30 % in the plant height of the bioindicator C. sativus, when submitted to the same fermented broth.…”
Section: Resultssupporting
confidence: 88%
“…This reduction, as a function of the fermented broth, was also observed by Brun et al (2016) on C. sativus plants at 7 days after the application of Phoma sp. Similarly, Klaic et al (2017), after optimizing the solid state fermentation process for the production of the bioherbicide through Phoma sp. secondary metabolites, also observed its phytotoxicity on C. sativus plants, with a reduction of 20 % in the fresh mass, in comparison to the control treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 g L -1 Fonte: Para et al 2005 Em seguida, os frascos foram mantidos a temperatura de 28°C e agitação de 120 rpm (Innova 44R, New Brunswick) por um período de 10 dias, de acordo com metodologia descrita por Klaic et al (2017) (Brasil, 2009).…”
Section: _____________________________________________________________unclassified
“…Naturally occurring substances can be applied for bioherbicide production [106,107]. SSF allows to obtain bioherbicides utilizing the agroindustry waste such as bagasse, soybean bran and corn steep liquor [108].…”
Section: Solid-state Fermentation (Ssf)mentioning
confidence: 99%